Comprehensive performance assessment on LBE-helium heat exchangers for the ADS based on extension theory - Keyong Cheng; Zhijiang Meng; Xunfeng Li; Junlin Chen; Xiulan Huai (Case Studies in Thermal Engineering, 2024)
Researches about comprehensive, systemic and multi-level assessment methods are limit. Therefore, a comprehensive assessment method of heat exchangers based on extension theory is proposed. Heat transfer, pressure drop, mechanism, safety and reliability, economy, structure, mechanism and production performance are considered and evaluated in detail. By using this method, the comprehensive performances of the shell-tube and printed circuit heat exchangers as the intermediate heat exchanger of the accelerator driven sub-critical system are evaluated for comparison. The results show that the economy performance and pressure drop for the shell-tube heat exchanger attain the highest grades because the processing technology is mature and flow velocity is lower. However, the structure performance parameter is the lowest level due to its large volume and mass. For the printed circuit heat exchanger, the safety and reliability performance attains the lowest grade due to its easily blocked mini-channels and the manufactured thin plate. However, the mechanism performance shows the highest grade. In addition, the pressure drop performance also attains the highest grade due to its large cross-sectional area and low flow velocity. In conclusion, the comprehensive performance of the printed circuit heat exchanger is theoretically better than the shell-tube heat exchanger.